PKM self compassion dan parenting untuk tahanan wanita di Lembaga Pemasyarakatan Kelas IIA Bolangi Sunguminasa Kabupaten Gowa - Widyastuty Widyastuty; Eva Meizara Puspita Dewi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
This service aims to provide the understanding among female prisoners so that they have sufficient insight in carrying out the role of the mother later after the prison. This study involved 30 female prisoners who had been selected by the prison staff themselves. The method used are self compassion therapy, psychoeducation and parenting discussion, and games for participants. Based on the results of the study, it can be concluded that there is an increase in the understanding of prisoners' participants about Self Compassion so that after this therapy female inmates appear fresher and accept themselves with their current conditions at the prison. Furthermore, for the psychoeducation of the mother's role in the ideal of parenting, participants have a tool to evaluate themselves with their roles so far and are eager to make changes in themselves to be the best mothers for children, especially when they leave prison later.